Patient perceptions of vulvar vibration therapy for refractory vulvar pain - Zolnoun, Denniz (2008)
The objective of this study was to describe acceptability of vulvar vibration therapy (VVT), a novel treatment approach to vulvodynia. We included women with vulvodynia who attended the Pelvic Pain Clinic and had used VVT for at least two weeks. Participants completed a three-page, 65-item, questionnaire assessing demographics, VVT usage and responses to Likert statements regarding accessibility, comfort and symptom response to VVT. Of 69 qualifying patients, results from 49 (72%) were eligible for analysis. Participants were primarily white, married and well-educated, with a median age of 30 (range 19–68 years). Median duration of vulvar pain and dyspareunia was two years (0–23) and three years (0–30), respectively. Median duration of VVT was five months (1–18) and three days per week (0.5–7). Fully, 83% said that, “vibrator treatment is an acceptable treatment”, 83% said that they were “satisfied with vibrator treatment”, 76% endorsed vibrator as comfortable to use, 73% indicated that sex is less painful since starting vibration treatment and 88% would recommend VVT to others. We conclude that the therapeutic rationale for VVT is based on the anti-nocioceptive properties of vibration and on the favorable response of vulvodynia to physical therapy. Vulvar vibration therapy is safe, inexpensive and, in this survey, acceptable to most patients, many of whom described improvement in symptoms.